SISTEM INFORMASI PENJUALAN ELECTRONIC COMMERCIAL STUDI KASUS CV. ZOOM COMPUTER - Suzan Agustri; Lastri Widya Astuti (UNIVERSITAS INDO GLOBAL MANDIRI)
CV. Zoom Computer is a private enterprise engaged in the sale of electronic goods. To resolve this issue Zoom Computer requires a good system and programmed the system to be more effective and efficient so as to optimize profitability. The problem of this study is limited to the design of electronic commercial sales information system with reference to the theories of commercial electronic design. The methodology in the design of electronic commercial sales information system is to implement the framework Waterfall. Using the programming language PHP and MySQL as a database manager application. CV. Zoom Computer using the Sales Information System Electronic Commercial is expected to facilitate the control and processing, the data inventory, purchasing, and sales and better payments so as to reduce the likelihood of potential errors in checking the information obtained will be faster and more accurate as well as a broad range.